2013
DOI: 10.1186/1757-2215-6-93
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GnRH agonist triggering and intensive luteal steroid support on live-birth rates and ovarian hyperstimulation syndrome: a retrospective cohort study

Abstract: BackgroundConventional luteal support packages are inadequate to facilitate a fresh transfer after GnRH agonist (GnRHa) trigger in patients at high risk of developing ovarian hyperstimulation syndrome (OHSS). By providing intensive luteal-phase support with oestradiol and progesterone satisfactory implantation rates can be sustained. The objective of this study was to assess the live-birth rate and incidence of OHSS after GnRHa trigger and intensive luteal steroid support compared to traditional hCG trigger an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
1
31
0
3
Order By: Relevance
“…Subsequently, a systematic Lack of availability of intramuscular progesterone, HCG dosing, or both, in some countries Patient characteristics limiting widespread use Premature Cochrane reviews and meta-analyses Misconceptions and resistance meta-analysis and a Cochrane review concluded that GnRHa should not be used routinely for final oocyte maturation in autologous cycles in view of the low pregnancy and live birth rates (Griesinger et al, 2006;Youssef et al, 2011). With the realization that the luteal phase was suboptimal, several approaches were subsequently suggested to improve pregnancy rates, ranging from intensive luteal phase steroid support (Engmann et al, 2006(Engmann et al, , 2008Iliodromiti et al, 2013aIliodromiti et al, , 2013bImbar et al, 2012), adjuvant low-dose HCG at the time of GnRHa trigger (Griffin et al, 2012;Shapiro et al, 2008Shapiro et al, , 2011aShapiro et al, , 2011b or at the time of oocyte retrieval (Humaidan, 2009;Humaidan et al, 2010Humaidan et al, , 2013aHumaidan et al, , 2013bIliodromiti et al, 2013aIliodromiti et al, , 2013b or during the luteal phase (Castillo et al, 2010;Humaidan et al, 2013aHumaidan et al, , 2013b as well as the use of luteal phase recombinant LH administration .…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…Subsequently, a systematic Lack of availability of intramuscular progesterone, HCG dosing, or both, in some countries Patient characteristics limiting widespread use Premature Cochrane reviews and meta-analyses Misconceptions and resistance meta-analysis and a Cochrane review concluded that GnRHa should not be used routinely for final oocyte maturation in autologous cycles in view of the low pregnancy and live birth rates (Griesinger et al, 2006;Youssef et al, 2011). With the realization that the luteal phase was suboptimal, several approaches were subsequently suggested to improve pregnancy rates, ranging from intensive luteal phase steroid support (Engmann et al, 2006(Engmann et al, , 2008Iliodromiti et al, 2013aIliodromiti et al, , 2013bImbar et al, 2012), adjuvant low-dose HCG at the time of GnRHa trigger (Griffin et al, 2012;Shapiro et al, 2008Shapiro et al, , 2011aShapiro et al, , 2011b or at the time of oocyte retrieval (Humaidan, 2009;Humaidan et al, 2010Humaidan et al, , 2013aHumaidan et al, , 2013bIliodromiti et al, 2013aIliodromiti et al, , 2013b or during the luteal phase (Castillo et al, 2010;Humaidan et al, 2013aHumaidan et al, , 2013b as well as the use of luteal phase recombinant LH administration .…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…Some authors have reported no reluctance to trigger ovulation in IVF cycles when plasma estradiol was in excess of 15,000 pg/ml, and with no instances of early OHSS being observed [ 27 ]. The risk for multiple pregnancies also appears to be signifi cantly decreased for the same reason: the gonadotropin surge triggers ovulation exclusively on a follicle of optimal maturity, whereas the prolonged duration of administered hCG action enables a greater number of dominant follicles to arrive at this critical maturity level and then to ovulate.…”
Section: Therapeutic Triggering Of Ovulationmentioning
confidence: 96%
“…Thus, supplementation with estradiol and progesterone may not be sufficient, as opposed to hCG with its LH-like activity. Indeed, studies demonstrated that the administration of 1,500 IU hCG 35 h after GnRHa triggering combined with micronized Progesterone resulted in a normalized luteal phase and a reproductive outcome similar to that of hCG triggering [11,14,26,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…However, optimal cryopreservation programs are not available worldwide, additional costs are incurred, patient satisfaction may decline and concerns are raised regarding epigenetic changes and reproductive outcomes [22]. Intense progesterone and estradiol supplementation have been proposed with conflicting results [4,16,[23][24][25][26]. Another strategy for luteal phase rescue after GnRHa triggering is adding low-dose hCG to estradiol and progesterone [27].…”
Section: Discussionmentioning
confidence: 99%